Effect of different levels of protein and energy supplementation in hoggets fed native pasture hay, regarding weight gain and hay consumption - Hall, George A.B.; Borges, F. Viterbo; Brondani, Luiz F. (Pesquisa Agropecuaria Brasileira, 2014)
In Santa Maria, Rio Grande do Sul, Brazil, the influence of different levels of protein and energy supplementation were studied, using sheep fed native pasture hay. Fifty-six Corriedale ewe hoggets weighing approximately 24 kg were adapted to individual wooden pens and fed native grass hay for 10 days. Two supplementary rations were prepared with cracked corn and soybean meal, to provide approximately 15 and 30% crude protein, and similar TDN levels. The hoggets were randomly distributed in seven treatments. Evenumbered treatments received the first ration, while odd-numbered treatments (with the exception of treatment 1) received the second ration. All animals were offered ad libitum native grass hay. The supplementary rations were fed once daily in separate feed bunks at the rate of 0, 75, 150 or 300 g per head. The experimental design allowed the study of protein and/or energy at various levels. Weight gain and hay consumption were measured on days 14, 29 and 54 of the trial. Mean weight gains over the whole trial, for treatments 1 through 7, were: 52.1, - 20.8, - 5.8, 25.5, 25.5, 48.6 and 75.2 g daily. The greatest gains were observed during the first period, when significant treatment differences were observed (P < 0.05). During the second period highly significant (P < 0.01) treatment differences occurred, but animals on those treatments receiving the lower levels of supplementary feed lost weight, while during the third period all treatments showed a loss in weight. Consumption of native grass hay showed a significant (P < 0.05) treatment effect only during the second period, with a tendency for hay consumption to decrease with higher levels of supplementation. When the effects of protein and energy supplementation were studied separately, it was evident that energy appeared to be a more critical factor than protein for the hoggets consuming native grass hay. These results and their implications toward extensive sheep production are discussed.